APPLICATION OF PROBLEM BASED LEARNING TO REDUCE MISCONCEPTIONS OF THE CONCEPT OF HEROES IN GRADE V STUDENTS OF SDN TEMANGGAL MAGELANG - Nur Aiman; Dhiniaty Gularso (Jurnal Cakrawala Pendas, 2026)
This research aims to overcome the misunderstanding of elementary school students in social studies learning, especially in the concept of heroes who tend to be understood narrowly as figures of the independence period who have passed away. This condition shows the need for a learning approach that is able to facilitate the development of deeper and meaningful conceptual understanding. This study aims to describe the application of the Problem Based Learning (PBL) model in reducing misunderstandings of the concept of heroes and analyze changes in students' understanding after participating in problem-based learning. This study uses a qualitative case study method involving grade V students of SDN Temanggal. The learning process is designed through PBL stages which include problem orientation, information exploration, group discussions, and digital project development with the theme "Contemporary Heroes". Data collection was carried out through pre-learning diagnostic tests, learning observations, and post-learning formative assessments. The results showed a large decrease in misunderstandings of about 45%, which was shown by the increased ability of students to distinguish historical heroes and contemporary heroes. In addition, students demonstrate improved critical thinking skills and the ability to articulate conceptual understanding independently. These findings confirm that the application of PBL integrated with digital media is effective in reducing conceptual misunderstandings and broadening students' understanding of the meaning of heroism. This study recommends the wider application of PBL in social studies learning to strengthen historical literacy and character development of elementary school students.